2018
DOI: 10.1177/1528083718811084
|View full text |Cite
|
Sign up to set email alerts
|

Thermal comfort properties of plasma-treated warp-knitted spacer fabric for the shoe insole

Abstract: Thermo-physiological comfort properties are crucial aspects of interlining material comfort for shoe insole which can be examined for permeability and conductivity. Air and water vapour permeability, conductivity and resistance of thermal are the main criteria for thermo-physiological comfort properties. Clothing comfort can be enhanced through special finishes including plasma which is one among the well known for surface modification. Oxygen and argon atmospheric plasma were used to analyse the comfort prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The thermal comfort of the textile material highly depends upon thermal resistance, which is affected by thickness of the fabric and thermal conductivity (Rajan and Sundaresan, 2020). Figure 1 (a, b, c) indicates the trilayer composite fabric, wool knit fabric and polyester nonwoven fabric, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The thermal comfort of the textile material highly depends upon thermal resistance, which is affected by thickness of the fabric and thermal conductivity (Rajan and Sundaresan, 2020). Figure 1 (a, b, c) indicates the trilayer composite fabric, wool knit fabric and polyester nonwoven fabric, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al [ 22 ] successfully prepared an elastic 3D conductive network using gold ion sputtering and cleverly designed channel cracks in the 3D sponge skeleton to achieve fast response time (9 ms), ultra-low detection limit (0.568 Pa), and good reproducibility over 1000 cycles, making it promising for biological motion and health monitoring applications. Spacer fabrics with three-dimensional are also being used in an increasing number of applications because of their excellent properties, such as sensing substrate materials [ 24 ], self-generating substrates [ 11 , 25 ], and protective cushioning layers for the human body [ 26 , 27 ]. Li et al [ 24 ] coated carbon black uniformly on a slightly cured silicone elastomer pre-adhered to the surface of a 3D fabric and fabricated a pressure sensor with good conductivity that can measure external pressure up to 283 kPa with a conductivity range of 9.8 kΩ and a sensitivity of 50.31 × 10 −3 kPa −1 , which is superior to other fabric-based pressure sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the good elastic recovery of the spacer fabric, the capacitive pressure sensor exhibited a sensitivity of 0.283 KPa −1 , fast response time and good cycling stability (>=20,000). Rajan et al [ 26 ] used the plasma treated spacer fabric as insoles and investigated their thermal comfort properties, showing that the spacer insole had good thermal physiological comfort as insoles. Kumar et al [ 27 ] used spacer fabric instead of foam in a motorcycle helmet liner and studied the breathability, heat, and water vapor resistance and compression properties of the spacer fabric, which showed that spacer fabric has better energy absorption, breathability, and evaporative heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Polyester fabric is largely used due to characteristics such as thermal stability, light weight, excellent resistance to washing, durability, and ease of dyeing. [ 19 ] Its main disadvantages are related to hydrophobicity, which makes it difficult to clean stains and hydrophilic dirt, [ 20 ] and poor adhesion when coated with polymeric films. [ 21 ]…”
Section: Introductionmentioning
confidence: 99%